Efecto de las fases lunares y estimulantes en la germinación y desarrollo inicial del cacao nacional en la granja Santa Inés - Solano Pereira, Isis Aurea (2009)
The present project on: Probable effects of the lunar phases in the emergency and cre-foundation of the plants coming from seed of national cocoa, treaty with consistent stimu-lants in water of dry and fresh coconut, and Cytokin; he/she was carried out it in the nurse-ry of cocoa of the Ability of Agricultural Sciences, University of Machala; with the follow-ing objectives: 1. To determine the effects of the moon phases on the germination and ini-tial development of the seed of cocoa; 2. To evaluate the behavior of the stimulants in the germination and initial development of the seed of cocoa; 3. To establish the economic analysis of the treatment. You programs the sowing of the seeds of national cocoa with the phases moon-head, for that which five stimulants (Cytokin, water of dry coconut, water of fresh coconut, Cytokin but water of dry coconut and Cytokin but water of fresh coconut) were used in which you includes an absolute witness; using the experimental design totally at random with four repetitions for the effects of the stimulants and an analysis combined for the lunar phases; the average comparison you employment the test of Duncan with a level of significance of 5% with the following variables: emergency percentage, percentage of fall of the cotyledons, growth in height until the 90 days, number of leaves for plan-ta, diameter of the shaft and weight of the system radicular. According to the obtained results the variance analysis was alone significant in the interaction of lunar phases for stimulants, the same ones that acted increasing the germination in front of a witness in approximately 35 to 40%, because of the activity of the citoquininas and auxinas, vitamins with-had in the coconut water. The conclusion of this project was that the adult numbers of leaves it was given in the lunar phase of the waning room and that the stimulants applied influence-rum on the rate of growth in longitude; the biggest shaft diameter you registration in plants sowed in new moon being increased in more than 100% with relation to the moon other phases and lastly the weight of roots was superior in the plants sowed in the phase of new moon.